2015
DOI: 10.3109/00207454.2015.1031749
|View full text |Cite
|
Sign up to set email alerts
|

The use of MMSE and MoCA in patients with acute ischemic stroke in clinical

Abstract: Neuropsychological performance of stroke patients was influenced by biological and demographic variables: age, diabetes and intracranial atherosclerosis. The MoCA and MMSE are both reliable assessments for the diagnosis of cognitive impairment after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…56 It has also been able to identify subtle but clinically relevant cognitive deficits with greater frequency than MMSE, especially in populations with MCI and chronic heart failure 57 and acute ischemic stroke. 58 The MoCA is designed to be more sensitive to minor cognitive deficits than the MMSE and thus may be a superior screening instrument for MCI and vascular AD, as well as chronic heart failure, stroke, and Parkinson disease. 59 In addition, the MoCA consists of subscales, including memory, executive function, attention, orientation, language, and visuospatial function, which increases the sensitivity of this instrument over the MMSE.…”
Section: Resultsmentioning
confidence: 99%
“…56 It has also been able to identify subtle but clinically relevant cognitive deficits with greater frequency than MMSE, especially in populations with MCI and chronic heart failure 57 and acute ischemic stroke. 58 The MoCA is designed to be more sensitive to minor cognitive deficits than the MMSE and thus may be a superior screening instrument for MCI and vascular AD, as well as chronic heart failure, stroke, and Parkinson disease. 59 In addition, the MoCA consists of subscales, including memory, executive function, attention, orientation, language, and visuospatial function, which increases the sensitivity of this instrument over the MMSE.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between contrasting groups with various degrees of severity of vascular cognitive impairment were highlighted in many studies 1419 , 24 , 31 , 41 , 45 , 46 , 49 , 58 , 60 , 62 , 66 However, studies need to improve the control of variables such as sociodemographic (age and education) and neurological data (cerebrovascular disease) that influence patient cognitive performance 446…”
Section: Discussionmentioning
confidence: 99%
“…Some studies support the high sensitivity of the MoCA18 , 46 , 51 , 54, but reveal its low specificity 1214 , 24 , 42 , 48 , 49 , 52 , 57 , 62 Chan et al12 found that 77% of patients were classified as cognitively intact on the MoCA but were impaired for one or more cognitive domains on a neuropsychological assessment (intellectual functioning, processing speed, and visual memory) not evaluated by the screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be attributed to that the sensitivity of MMSE is slightly lower than MoCA as screening test for detection the cognitive impairment particularly processing speed and executive function. MMSE is less capable of testing for complex cognitive impairments in domains such as visuospatial, executive function, and abstract reasoning that are commonly affected in stroke patients [26].…”
Section: Discussionmentioning
confidence: 99%